The Effect of Competence and Job Placement Fit on Employee Performance, with Motivation as a Mediating Variable Among Employees of The Secretariat General, Ministry Of Villages - Ambarwati, Tri; Herawati, Aty (Universitas Pamulang, 2026)
Indonesia's Golden Vision 2045 transformation is hindered by low Civil Service Apparatus performance quality, where 35 percent of civil servants perform poorly and only 19.82 percent work optimally. Employee Performance Target data at the Ministry of Villages and Disadvantaged Regions shows fluctuation in